THE IMPLEMENTATION OF INTERACTIVE IMAGE MEDIA IN ENHANCING ARABIC LEARNING MOTIVATION AMONG PARTICIPANTS OF MUKHOYYAM ARABI AT UNIVERSITI ISLAM SELANGOR MALAYSIA - Safira Aulia; R. Taufiqur Rochman; Nur Hasaniyah; Muhammad Farhan bin Mat Noradin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of interactive image media in Arabic language learning, identify supporting and inhibiting factors, and examine its contribution to students’ learning motivation in the Mukhoyyam Arabi program at Universiti Islam Selangor Malaysia. The study employs a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and documentation involving facilitators and participants of the program. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of interactive image media is carried out systematically through several stages, including opening activities, vocabulary introduction, audio utilization, visual presentation of images, and evaluation through interactive activities. The use of this media creates an engaging and dynamic learning environment that enhances students’ interest and participation. Supporting factors include high student enthusiasm, enjoyable learning atmosphere, cross-cultural interaction, and the active role of facilitators. Meanwhile, inhibiting factors consist of limited program duration, differences in students’ backgrounds, and the need for initial adaptation. Overall, interactive image media significantly contributes to improving students’ learning motivation, as indicated by increased interest, attention, and active engagement during the learning process.